Assessing the Predictive Power of Net Income and Inventory on Operating Cash Flows: A Study of Food and Beverage Companies in Indonesia - Laksana, Rio Dhani; Shaferi, Intan; Naznii, Humaira (Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study investigates the ability of net income and inventory changes to predict future operating cash flows in manufacturing companies within Indonesia’s food and beverage sector. Using a sample of firms listed on the Indonesia Stock Exchange from 2022 to 2025, the study employs multiple regression analysis to examine the partial and simultaneous effects of these variables. The results show that net income has a significant positive impact on future operating cash flows, indicating its usefulness for investors and stakeholders in financial decision-making. However, changes in inventory do not significantly affect future operating cash flows, suggesting limited predictive value in this context. Simultaneous testing reveals that net income and inventory changes together significantly influence future operating cash flows. The findings underscore the importance of focusing on profitability indicators when assessing cash flow potential in this industry.